Activity profiling of peptidases in Angiostrongylus costaricensis first-stage larvae and adult worms. - Karina M Rebello; James H McKerrow; Ester M Mota; Anthony J O Donoghue; Ana Gisele C Neves-Ferreira (Public Library of Science (PLoS), 2018)
BACKGROUND:Angiostrongylus costaricensis is a relatively uncharacterized nematode that causes abdominal angiostrongyliasis in Latin America, a human parasitic disease. Currently, no effective pharmacological treatment for angiostrongyliasis exists. Peptidases are known to be druggable targets for a variety of diseases and are essential for several biological processes in parasites. Therefore, this study aimed to systematically characterize the peptidase activity of A. costaricensis in different developmental stages of this parasitic nematode. METHODOLOGY/PRINCIPAL FINDINGS:A library of diverse tetradecapeptides was incubated with cellular lysates from adult worms and from first-stage larvae (L1) and cleaved peptide products were identified by mass spectrometry. Lysates were also treated with class specific peptidase inhibitors to determine which enzyme class was responsible for the proteolytic activity. Peptidase activity from the four major mechanistic classes (aspartic, metallo, serine and cysteine) were detected in adult worm lysate, whereas aspartic, metallo and serine-peptidases were found in the larval lysates. In addition, the substrate specificity profile was found to vary at different pH values. CONCLUSIONS/SIGNIFICANCE:The proteolytic activities in adult worm and L1 lysates were characterized using a highly diversified library of peptide substrates and the activity was validated using a selection of fluorescent substrates. Taken together, peptidase signatures for different developmental stages of this parasite has improved our understanding of the disease pathogenesis and may be useful as potential drug targets or vaccine candidates.